Never the roses - Lambert, Jennifer K., 1966- (Bramble, Tor Publishing Group, 2025)
The Dread Sorceress Oneira has retired. She's exhausted from fighting the endless wars of kings and queens and expects death soon. Alone except for a mythical wolf, a goddess's avatar, and a magical cat, Oneira grows bored and impulsively steals a book from her old rival, Stearanos. The theft sparks an unlikely exchange of witty notes that blossoms into something deeper. But Stearanos is bound to a wicked king now at war with the queen Oneira once served, forcing her to choose between connection and conflict.